Has the COVID-19 pandemic changed gender- and parental-status-specific differences in working from home? Panel evidence from Germany - Anja-Kristin Abendroth; Yvonne Lott; Lena Hipp; Dana Müller; Armin Sauermann; Tanja Carstensen (Gender, Work & Organization, 2022)
Has COVID-19 changed gender- and parental-status-specific differences in working from home? To answer this question, we used data from the Institute for Employment Research High-Frequency Online Personal Panel collected in Germany in the early stages of the pandemic (May–August 2020). Regression analyses revealed changes in pre-pandemic gender- and parental-status-specific differences in remote working—not only when strict social distancing measures were in place, but also after they were lifted: Fathers were no longer more likely than childless men and women to work remotely, and women were no longer more likely than men to work more hours from home when using this arrangement. Further, the results suggest that cultural barriers in organizations to working from home—which were especially prevalent for mothers before the pandemic—have decreased.
Keywords: 300; COVID-19; gender; parental status; remote working; working from home